The sentometrics toolbox: Enriching decision-making with sentiment information from news articles and corporate disclosures - (:unkn) unknown (My University, 2025)
The sentometrics toolbox: Enriching decision-making with sentiment information from news articles and corporate disclosures
Keywords: Textual-sentiment; machine learning; econometrics; factor models